Recruitment and selection process of ITAL Adweg (Pvt) Ltd. - Nasir, Taiyeba (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.